Impact of Holmium and Nickel Substitution on Y-Type Hexagonal Ferrites Synthesized via Sol-gel Method - Manzoor, Alina; Shahzad, Aamir; Arshad, Muhammad Imran; Muhammad Afzal, Amir; Shinwari, Tauqir; Khan, Muhammad Yaqoob (Journal of Materials and Physical Sciences, 2023)
Sol-gel auto combustion route is employed to fabricate Y-type hexagonal ferrites Ba2-xHoxSr2-yNiyFe12O22(x = 0, 0.02, 0.04, 0.06, 0.08, 0.1 & y = 0, 0.1, 0.2, 0.3, 0.4, 0.5). All prepared samples are examined through XRD, SEM, and dielectric characterization.The prepared samples were then sintered at 950 °C for 6 hours. TGA analysis was carried out to find the estimated sintering temperature for the phase development. The XRD experiment was performed to determine the effect of substitution on structural parameters. XRD crystallite size was observed in the range of 5.5 – 19.79 nm. Lattice constant (a) was found in the range 6.08 – 6.17 Å, and that of c was found in the range 44.08 – 44.73 Å. The averagegrain size value wasnoted to be around ~ 2?m as calculated through SEM.Through Raman spectroscopy, six active modes (3E1g, 2A1g, and E2g) correspond to different vibrational modes of the prepared samples. LCR technique showed that the dielectric constant and the dissipation factor were decreased with increased frequency. A decrease in dielectric losses suggests these materials are for high-frequency applications.